RELASI ASAS LEGALITAS HUKUM PIDANA DAN PEMIKIRAN HUKUM ALAM - Vincentius Patria Setyawan; Hyronimus Rhiti (Sekolah Tinggi Pariwisata Mataram, 2022)
This research is motivated by legal problems/issues related to the position of natural law related to the application of the principle of legality. The emergence of the principle of legality which later developed into a fundamental principle and is firmly held in the enforcement of criminal law is in line with the development of the flow of positivism. The principle of legality has a close relationship with positivism, if positivism emphasizes that outside the written legislation there is no law, then the principle of legality also determines that outside the rules of criminal law there is no criminal law. The close relationship between the principles of legality and positivism has given birth to a legal certainty in providing protection to criminals so that they are not treated arbitrarily by the rulers (kings) and judges. However, a problem arises that cannot be answered with positivism and the principle of legality which puts forward the written form of law as the only legal basis for convicting someone, namely when the development of crime is faster than the development of the law. Based on these conditions, it would be necessary to re-examine natural law, which actually contains general principles for the application of a more basic law, not only emphasizing the written aspect of the law. This research is a normative legal research that examines the legal principle, namely the principle of legality against natural law. This study of the principle of legality uses a conceptual approach by studying the doctrines/theories regarding the principle of legality to find out the study of natural law on the principle of legality, in order to provide a critique of the limitations of the principle of legality in accommodating the development of criminal acts. The results of this research are prescriptive, namely answering the problem by providing a proper solution (das sollen) to the formulation of the ideal legality principle to accommodate the development of criminal acts.